Case management as an opportunity for healthcare: user experiences - Chaparro-Díaz, Lorena; Valbuena-Castiblanco, Cindy Lorena; Carreño-Moreno, Sonia; Hernández-Zambrano, Sandra Milena; Carrillo-Algarra, Ana Julia (Revista Cuidarte, 2023)
Highlights:• Case management allows nurses to have visibility of their professional role, where personalized education, care plan and timely communication.• Case management must consider the dyad: person with chronic disease and family caregiver (may be a principal) to reconcile the care plan and agree on therapeutic goals.• The care encounter is characterized by a 40-minute assessment, a visit from 30 minutes to 2 hours, and subsequent follow-up meetings on demand.• Technological tools are an important part of the implementation of case management in nursing.Introduction: People with multimorbidity and their caregivers are beginning to be recognized as emerging subjects of health systems.  In Colombia there is no differentiated approach to care for this population, as well as its health-disease process.  Objective: To understand the experience of people with multimorbidity and their caregivers after receiving a case management intervention.  Methods and materials: It is a qualitative study in which 33 participants among people with multimorbidity and their caregivers who received intervention with case managers were interviewed, a comparative analysis and use to tools analytics grounded theory. Results: There are 3 dimensions that are, the actors where nursing becomes relevant as a reliable source of care; the Care Meeting, as a space created within case management to maintain trust and; Results in the health system, where the need to integrate this type of outbreak into the Colombian Health Model is confirmed. Discussion: Complementary qualitative evidence data from the central study with a greater impact on the quality of care through the therapeutic relationship at home. Conclusion: The dyad requires home support for self-management of the disease based on trust, empathy, empowerment and administrative management carried out by case managers.How to cite this article: Chaparro-Diaz, Lorena; Valbuena-Castiblanco, Cindy Lorena; Carreño-Moreno, Sonia; Hernández-Zambrano, Sandra Milena; Carrillo-Algarra, Ana Julia. Case management as an opportunity for healthcare: user experiences. Revista Cuidarte. 2023;14(3):e2923. http://dx.doi.org/10.15649/cuidarte.2923
Keywords: Multimorbidity; Caregivers; Family; Case Management; Qualitative Research